Equilibrium and Inefficiency in a Community Model With Peer Group Effects - Charles A. M. de Bartolome (Journal of Political Economy, 1990)
Public-service output depends on input expenditures, on own personal characteristics, and on the characteristics of the other residents in the community (the peer group effect). In a community model with public expenditures set by voting, with migration between communities, and with land price differentials (capitalization), it is shown that communities may become heterogeneous in composition and (second-best) inefficient. This equilibrium occurs when the peer group effect is neither "too strong" nor "too weak." The inefficiency arises because an externality is created by migration. The land price differential does not play the part of the "price" of the better peer group but of a transfer payment.